Reproductive biology of Charybdis (Goniohellenus) longicollis Leene, 1938 (Brachyura: Portunidae), in the north-eastern Mediterranean Sea, Turkey - Tureli, Canan; Nur Yesilyurt, Irem (Indian Journal of Fisheries, 2019)
The swimming crab, Charybdis (Goniohellenus) longicollis Leene, 1938, is a Lessepsian migrant into the Mediterranean and little is known about its biology in Iskenderun Bay, north-eastern Mediterranean, Turkey. The size of crabs, sex-ratio and spawning period of this species was defined from 951 specimens in order to understand their reproduction and development in the NE Mediterranean Sea. The crabs were found to occur throughout the year. Carapace width (CW) ranged between 7.22 to 100.60 mm and total weight ranged from 1.34 to 164.09 g. Male-female sex ratio was 0.6:1. Highest gonado-somatic index (GSI) was seen in March and September for females and in May for males. Ovigerous females were present throughout the year, with peak spawning activity in July and September. The CW of the ovigerous female crabs ranged between 23.71 and 95.93 mm. In winter months, GSI of males and females decreased. However, spawning season of C. (G.) longicolis in YumurtalÄ±k Cove was observed throughout the year.Â Keywords: Charybdis (Goniohellenus) longicollis, Crustacea, Iskenderun Bay, Lessepsian, Portunidae, Reproductive biology